From Honeycomb- to Microsphere-Patterned Surfaces of Poly(Lactic Acid) and a Starch-Poly(Lactic Acid) Blend via the Breath Figure Method. Issue 1 (26th January 2017) - Duarte, Ana Rita C.; Maniglio, Devid; Sousa, Nuno; Mano, João F.; Reis, Rui L.; Migliaresi, Claudio
Background: This study investigated the preparation of ordered patterned surfaces and/or microspheres from a natural-based polymer, using the breath figure and reverse breath figure methods. Methods: Poly(D, L-lactic acid) and starch poly(lactic acid) solutions were precipitated in different conditions – namely, polymer concentration, vapor atmosphere temperature and substrate – to evaluate the effect of these conditions on the morphology of the precipitates obtained. Results: The possibility of fine-tuning the properties of the final patterns simply by changing the vapor atmosphere was also demonstrated here using a range of compositions of the vapor phase. Porous films or discrete particles are formed when the differences in surface tension determine the ability of polymer solution to surround water droplets or methanol to surround polymer droplets, respectively. In vitro cytotoxicity was assessed applying a simple standard protocol to evaluate the possibility to use these materials in biomedical applications. Moreover, fluorescent microscopy images showed a good interaction of cells with the material, which were able to adhere on the patterned surfaces after 24 hours in culture. Conclusions: The development of patterned surfaces using the breath figure method was tested in this work for the preparation of both poly(lactic acid) and a blend containing starch and poly(lactic acid). The potential of these films to be used in the biomedical area was confirmed by a preliminary cytotoxicity test and by morphological observation of cell adhesion.